På arvens fang, i den ubrutte linjens favntak? Om donorfamilier og adoptivfamilier og tetting av genetiske og biografiske hull - Fjell, Tove Ingebjørg (Tidsskrift for kulturforskning, 2003)
In society today, there is considerable interest in genetic inheritance. There appears to be a strong conception that knowledge of continuity and unbroken lineage is important. In this article I query whether this is the case in families whose children have been adopted or have been conceived through sperm or egg donation. What are the notions within these two groups with respect to parenthood and kinship, continuity and unbroken lineage? The article concludes that the adoptive families are concerned with backtracking in order to plug biographical holes - achieved not by tracing the children`s genetic families, but by visiting their native country. Place is important. The donor group is more diverse. Lesbian donor families are often given whatever information there might be, however scant, in order to facilitate the child's effort to build his or her biography. Heterosexual donor families are given the choice by health professionals to keep the donation secret vis-ÃƒÂ -vis the child and everyone else. Some of the heterosexual couples have virtually no interest at all in inheritance and genetics.